Public sector auditing: issues underlying the audit of public enterprise / Garan Ak Malina - Ak Malina, Garan (1991)
Public enterprises provided the goverment with machinery to achieve the objectives of New Economic Policy with the advent of the Second Malaysia Plan(1971- 1975) . Thus far billions of dollars has been invested for the enterprises to carry out their activities. In the process, due to mismanagement and incapabilities to cope with rapid development, some of the enterprises continually not meeting its targeted objectives. The issues connected to audit of public enterprises cannot ' escape the question of accountability. This is because to determine accountability, there must be an examination on the general set up of an organisation, its abjective and its operation. Thus creating question on the conduct of audit by the Auditor—General's Office. The data needed for this research paper are mainly from secondry data. The constitution and acts relating to incorporation maintaining of accounts and audit were considered. The Economic Reports, Auditor General Reports, Malaysian Plan Review and Budget Reports provides the factual figures for the analysis. The journals, textbooks and seminar papers provides the ideas to approach the issues. After taking into ac counts all the above the finding can be briefly summarise here. The constitution and the act provides a comprehensive ways into which the audit issues can be traced. It gave full responsibility to the Auditor General for the audit of all public enterprises except for certain Off Budget Agencies. The conduct of financial and compliance audit which focus mainly on the certification of annual reports. The transitional nature of audit to the implementation of performance auditing involves careful deliberation. There a,re arguments as to adoption of forms of measurements for each elements of the performance auditing. Finally, the manner of the appointment of Auditor General for which attracts issues regarding his standing with the Parliament. The paper also considers the independence of the Auditor-General in all aspects of his audit of public enterprises.